Implementasi Fungsi Mal Dan Fungsi Tamwil Pada Baitul Mal Wa Tamwil (Studi Kasus BMT UGT Sidogiri Kota Malang) - Muhammad Saiful Kalam; Titis Miranti (Universitas Islam Nahdlatul Ulama Jepara, 2023)
BMT UGT Sidogiri was ranked 6th out of the 100 largest cooperatives in Indonesia in 2019. This is an interesting achievement to study. The study in this research is the implementation of mall and tamwil functions in terms of juridical, organizational and operational aspects. The research was located at the BMT Malang City Branch. The type and research approach used qualitative case studies. Data collection techniques used observation, interviews and documentation. Based on the research results, the juridical aspect explains that BMT UGT Sidogiri has had a cooperative legal entity since 2000. The organizational aspect explains that the implementation of the mall function is controlled and controlled by Amil Zakat Institution of Sidogiri, Pasuruan, while the tamwil function is controlled by BMT for each office. Tamwil operational activities are carried out in accordance with existing procedures and provisions. In addition, the mall's operational activities include the distribution of social funds such as zakat gifts, house renovations, scholarships, and so on. The conclusion of this research is that BMT Malang City Branch has implemented the mall function and its tamwil function simultaneously. The implication is that this research can be used as a reference and point of reference for future researchers who study the implementation of mall and tamwil functions in BMT in terms of juridical, organizational and operational aspects. This research also complements aspects of previous research which only included one or two aspects